Against the lexical view of cumulative inferences - Wehbe, Jad (Proceedings of Sinn und Bedeutung, 2023)
Ionin and Matushansky (2002) propose, based on data from comitatives in Russian, that distributivity is associated only with the spec,TP position. In this paper, I (i) present data from the Lebanese Arabic double subject construction that supports Ionin and Matushansky’s conclusion that the availability of distributive readings is sensitive to syntactic position and (ii) argue for a novel theory of how this arises. In particular, I propose that pluralization operators are the only sources of cumulative inferences and that they are restricted in distribution such that they can only apply to predicates derived by movement and never to lexical predicates. I show that this predicts a set of facts from the double subject construction all indicating that there is a relationship between the availability of a distributive reading over a DP and whether that DP moves. This proposal argues against an influential approach where cumulativity is taken to be an inherent property of lexical predicates (Krifka 1992; Kratzer 2008).